Encryption techniques & access control models for data security: A survey - Dixit, Rashmi; Ravindranath, K. (International Journal of Engineering and Technology, 2017)
In the process of sending information from sender to receiver, an unauthorized user may work in an active way (update it) or passive way (read or delay in sending). There must be some techniques which assures receiver that whatever information received from authorized user as well as must be same as sent from sender side, in addition to this receiver never make Denial of service. Nowadays sharing of information or resources is a very common thing from single user to the network to the cloud. When information is moving from one node to another node, security is a big challenge. When information is stored on the user’s computer, it is under control but when it is in movement user lose control over it. In the world of security, to convert information from one form to another form, Encryption is used, so that only authorized party will able to read. Encryption is a technique for any security-conscious organization.In this paper, we present basic access control models along with encryption techniques.